Relative effectiveness of sunitinib versus everolimus in advanced pancreatic neuroendocrine tumors: an updated matching-adjusted indirect comparison. (31st August 2018) - Ishak, K Jack; Rael, Michael; Hicks, Meagen; Mittal, Sangeeta; Eatock, Martin; Valle, Juan W
Aim: A matching-adjusted indirect comparison (MAIC) of sunitinib and everolimus has been previously reported based on the RADIANT-3 everolimus trial. We performed an analysis using updated overall survival (OS) data based on sunitinib's trial (A6181111).Methods: The MAIC matched on all baseline characteristics available from both studies. An anchored MAIC was performed for progression-free survival (PFS); an unanchored analysis was deemed more appropriate for OS due to crossover in both trials. A hazard ratio for sunitinib versus everolimus was derived from adjusted (weighted) sunitinib effects compared with the observed results for everolimus.Results: The adjusted hazard ratio for sunitinib versus everolimus was 0.85 (0.39–1.89) for PFS and 0.82 (0.53–1.27) for OS.Conclusion: Findings indicate comparable PFS and OS with sunitinib and everolimus.